2023
DOI: 10.1093/plphys/kiad213
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of maize root hydraulic architecture underlies highly diverse water uptake capacities

Abstract: Plant water uptake is determined by the root system architecture and its hydraulic capacity, which together define the root hydraulic architecture. The current research aims at understanding the water uptake capacities of maize (Zea mays), a model organism and major crop. We explored the genetic variations within a collection of 224 maize inbred Dent lines and successively defined core genotype subsets to access multiple architectural, anatomical, and hydraulic parameters in the primary root (PR) and seminal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…Another one is the variation in radial root hydraulic conductance between different lines in their response to environmental change. In fact, a recent study found significant genetic variations in radial hydraulic conductivity of 224 maize inbred lines (Rishmawi et al, 2023). The importance of root traits in water uptake has been intensively studied over the past decades (Javaux et al, 2013;Lynch, 2013;Lynch, 2019;Postma et al, 2014), but Fig.…”
Section: Root Water Uptakementioning
confidence: 99%
See 3 more Smart Citations
“…Another one is the variation in radial root hydraulic conductance between different lines in their response to environmental change. In fact, a recent study found significant genetic variations in radial hydraulic conductivity of 224 maize inbred lines (Rishmawi et al, 2023). The importance of root traits in water uptake has been intensively studied over the past decades (Javaux et al, 2013;Lynch, 2013;Lynch, 2019;Postma et al, 2014), but Fig.…”
Section: Root Water Uptakementioning
confidence: 99%
“…5 is averages over the two sampling points rather than values at any specific time. While water uptake by roots in different soil layers is dynamic and varies instantly following a change in environment (Maurel et al, 2010;Rishmawi et al, 2023), for phenotyping roots and identifying the difference in root water uptake between different varieties in the field, the proposed method for calculating average root water uptake over two sampling time points is sufficient.…”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…However, different measurement methods may produce different results, especially when comparing methods that rely on a hydrostatic driving force for water flow against those using an osmotic one (Kim et al, 2018 ). Additionally, empirical studies have shown that root hydraulic properties can strongly vary (up to orders of magnitude) among species (Bramley et al, 2009 ; Pratt et al, 2010 ; Steudle, 2000a ), but also among genotypes of one species (Rishmawi et al, 2023 ) or even among individuals of the same genotype (Steudle, 2000a ). This large variability can be explained, at least partially, by the function of roots as hydraulic rheostats, that is, the dynamic changes that root hydraulic properties undergo during development and in response to environmental stimuli (Maurel et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%